CYBERSECURITY AND INTERNATIONAL RELATIONS: EMERGING THREATS AND POLICIES - Yasmeen Naz (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Cybersecurity is vital to international relations, impacting global security, economic stability, and diplomacy. Its governance relies on international cooperation, highlighted by frameworks like the Budapest Convention and UN-led initiatives promoting responsible state behavior in cyberspace. However, geopolitical tensions and the involvement of diverse actors, including states and private entities, complicate effective governance. High-profile cyberattacks, such as ransomware and state-sponsored operations, expose critical infrastructure vulnerabilities and the potential for escalated conflicts.Key state actors like the U.S., China, and the EU significantly shape cybersecurity policies. The U.S. focuses on protecting critical infrastructure and forming coalitions, though surveillance controversies undermine trust. China prioritizes cyber sovereignty and strict domestic regulation but faces credibility issues due to espionage allegations. The EU emphasizes regulatory standards, such as GDPR, yet struggles with fragmented enforcement. Non-state actors, including tech companies and international organizations, play critical roles through innovation and norm advocacy but encounter challenges like profit motives and complex regulations.Emerging technologies, such as quantum computing and AI, intensify cybersecurity risks. Addressing these threats demands global standards, advanced technologies, and ethical frameworks. Multilateral collaboration and inclusive governance are essential to securing digital infrastructures, ensuring resilience, and fostering stability in an interconnected world.